Dendritic Cell as Potential Immunotherapy for Nasopharyngeal Cancer: A Review - Albertus Budi Sulistya; Rima Haifa; Geofanny Facicilia; Kristin Talia Marbun; Marsya Nilam Kirana; Yussy Afriani Dewi; Cynthia Retna Sartika; Andi Wijaya; Keri Lestari Dandan (The Indonesian Biomedical Journal, 2023)
BACKGROUND: Dendritic cell (DC)-based cancer therapy is a promising adjuvant therapy for nasopharyngeal cancer (NPC) after chemoradiation. Owing to low immunity after chemoradiation, DC therapy activates immune responses. Moreover, DC-based cancer therapy can decrease tumor progression, prolong lifespan, and increase the quality of life of patients. Various studies regarding the use of DC therapy for NPC have been reported, however there are limited reviews on the implementation and foundation of DC immunotherapy to expand this technology.METHODS: A literature search was performed on EMBASE, ScienceDirect, PubMed (MEDLINE), and Cochrane Library, with the term dendritic cells therapy for nasopharyngeal cancer, dendritic cell immunotherapy in nasopharyngeal cancer patients, and DC therapy in NPC, as the search keywords.RESULTS: A total of 199 literatures were reviewed, and four clinical trials were identified as relevant for this review. DC vaccines can be processed with various maturation and activation processes. Selected literatures reported antigens used when incubating the DC are latent membrane protein (LMP) 1, LMP2, and Epstein–Barr virus nuclear antigen 1 (EBNA1). Although DC therapy was produced from different pathways, it has been reported that there are increases of cluster of differentiation (CD)8+ T cells, CD4+ T cells, and the progression free survival (PFS) rate in DC immunotherapy patients than the radiochemotherapy patients.CONCLUSION: It can be concluded that DC could be used as an adjuvant therapy alongside the standard therapy of NPC, which prolongs NPC patient survival.KEYWORDS: adjuvant cell therapy, nasopharyngeal cancer therapy, dendritic cells